2006
DOI: 10.1177/153537020623100201
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Apoptosis with Dietary Bioactive Agents

Abstract: Apoptosls, a form of programmed cell death, Is a pivotal defense against the occurrence of cancer and is essential to metazoans In maintaining tissue homeostasis. Apoptosls exhibits a distinctive phenotype and Involves elimination of potentially deleterious cells. Many diseases have been associated with aberrantly regulated apoptotlc cell death, ultimately leading to Inhibition of apoptosls and propagation of diseases such as cancer. Elucidation of the critical events associated with carcinogenesis provides th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
95
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 116 publications
1
95
0
2
Order By: Relevance
“…The search for promising agents that could reduce the incidence and the burden of cancer has become increasingly important in recent years. Naturally occurring dietary supplements and herbs have stimulated great interest because of their chemopreventive and chemotherapeutic properties as well as their relatively non-toxic effects, low cost and availability as oral formulations (41)(42)(43)(44). Scutellaria barbata used in Chinese medicine has been shown to provide protection against several major liver, lung, and rectal cancers (17,45).…”
Section: Discussionmentioning
confidence: 99%
“…The search for promising agents that could reduce the incidence and the burden of cancer has become increasingly important in recent years. Naturally occurring dietary supplements and herbs have stimulated great interest because of their chemopreventive and chemotherapeutic properties as well as their relatively non-toxic effects, low cost and availability as oral formulations (41)(42)(43)(44). Scutellaria barbata used in Chinese medicine has been shown to provide protection against several major liver, lung, and rectal cancers (17,45).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional plant medicines have been used for centuries in different regions of the world. Despite insufficient evidence to support its therapeutic efficacy, the use of herbal medicine has increased considerably due to the relatively non-toxic effects, low cost and availability of these treatments (35,36). Fructus Xanthii, which is commonly used in Chinese medicine, was reported to have inhibitory effects on mast cell-mediated allergic reaction (37), as well as anti-inflammatory actions in lipopolysaccharide-stimulated inflammatory responses (38).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, a growing body of evidence demonstrates that current cancer therapies, such as chemo-, radio-, immuno-or suicide gene-therapy, primarily exert their antitumor effect by triggering apoptosis in cancer cells (Fulda and Debatin, 2004). However, cancer cells use multiple pathways to evade apoptosis, which underlie the insufficiency of current therapies (Khan et al, 2006;Martin, 2006). Therefore, searching for bioactive agents with the ability to induce apoptosis in cancer cells is a promising option for cancer chemoprevention and/or chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Though the presence of huge amounts of saponin compounds in N. sativa has been reported, any study regarding their anti-cancer activity has not been reported yet.Based on the abovementioned studies and considering the fact that in some cases herbal extracts are showing more potency than the purified components (Seeram et al, 2004;2006), this study was undertaken. We investigated the anti-proliferative potentiality of the crude saponin extract of N. sativa on human colon cancer cells, HCT116, and further elaborated the molecular mechanism underlying this action.…”
Section: Introductionmentioning
confidence: 99%